Novel Analytical Method Development, Validation and Stability Study of Anticancer Drug Erlotinib in Tablet Dosage Form by RP-UFLC - Purvini, K; IA, Chethan; Vaijanathappa, Jaishree (Indian Journal of Pharmaceutical Education and Research, 2021)
Present work is aimed to develop a novel, simple and accurate reverse phase-ultrafast liquid chromatographic (RP-UFLC) method for erlotinib (ELB) in tablet dosage form. The chromatogram was achieved by using Eclipse plus C18 column with methanol and water along with triethylamine (TEA 0.1%) as mobile phase (50:50 v/v) at a flow rate of 1 ml/min. The tablet dosage form was assayed, validated and subjected to degradation studies. The standard ELB possessed a retention time of 5.51 min and the developed method was linear in the concentration range of 10-100 µg/ml with r2≤0.99. Validation parameters have shown that the developed method was precise (%RSD < 1), accurate (recovery 98.50 to 99.52%) and robust. In the degradation studies, no extra products were observed in thermal conditions and a degraded product was observed in negligible percentage in basic and acidic conditions.
Keywords: Erlotinib; Accuracy; Precision; Robustness; Degradation study